1996
DOI: 10.1103/physrevc.54.737
|View full text |Cite
|
Sign up to set email alerts
|

4π studies of the 1.8–4.8 GeVHe3+nat

Abstract: The Indiana Silicon Sphere 4 detector has been used to measure light-charged particles and intermediatemass fragments ͑IMFs͒ emitted in the 18-4.8 GeV 3 Heϩ nat Ag, 197 Au reactions. Ejectile multiplicity and total event kinetic energy distributions scale systematically with projectile energy and target mass, except for the nat Ag target at 3.6 and 4.8 GeV. For this system, a saturation in deposition energy is indicated by the data, suggesting the upper projectile energy for stopping has been reached. Maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…However, when source mass corrections are made, the energy per nucleon distributions are very similar for both targets [40]. The projectile-target effect on the saturation of excitation energy with beam energy is in good agreement with INC calculations [30,41] for this lower momentum, complex projectile. The lower right-hand frame of Fig.…”
Section: Excitation Energy Depositionsupporting
confidence: 63%
See 2 more Smart Citations
“…However, when source mass corrections are made, the energy per nucleon distributions are very similar for both targets [40]. The projectile-target effect on the saturation of excitation energy with beam energy is in good agreement with INC calculations [30,41] for this lower momentum, complex projectile. The lower right-hand frame of Fig.…”
Section: Excitation Energy Depositionsupporting
confidence: 63%
“…This need was a primary motivation for the moving-source fits to the spectra. From moving-source analyses of all the spectra from the 1.8-4.8 GeV 3 He + 197 Au reaction [41], it was concluded that a sharp cutoff approximation gave a satisfactory account of the fraction of thermal events in the spectra. The thermal cutoff values were:…”
Section: Calorimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Preequilibrium or prebreakup emissions are likely explanations for high-energy components in light-particle spectra [4,10,20,21]. In some cases, the excess kinetic energies have been ascribed to collective flow even though a characteristic proportionality to the fragment mass is not evident in the data [11,22,23].…”
mentioning
confidence: 99%
“…1 Separating the equilibrium events from those having a nonequilibrium origin (outside the dotted lines in Fig. 1) must be done empirically from analysis of the spectra [7].…”
Section: Experimental Signalsmentioning
confidence: 99%